(untitled) (Indian Journal of Nematology, 2024)
Pot culture experiment was carried out under glass house condition to evaluate the resistance/tolerance of seven varieties of vegetable cowpea against Meloidogyne incognita. The variety Kadakkal local found as resistant with gall index 1 and all other varieties were highly susceptible to M. incognita. A field experiment was carried out to study the comparative effect of bio agents (Purpureocillium lilacinum and Stenotrophomonas maltophilia) and organic amendment (neem cake) in comparison with chemicals fluopyram and carbosulfan for the management of M. incognita in cowpea. All the treatments increased yield and reduced nematode population compared to untreated. Among the treatments, P. lilacinum cfu 2×106 @ 10 g/m2 in combination with neem cake @ 50 g/m2 and fluopyram 400 SC @ 250 g a.i./ha were statistically on par in increasing yield (53.70-54.63 %) and reducing nematode population in soil (93.03-94.27 %) and root (86.94-88.31 %).